2016
DOI: 10.1021/acs.jpcc.6b06732
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Stabilized Ir3– in a Superconducting Potassium Iridide

Abstract: The first charge-separated iridide (Ir3–) in an extended solid was identified at elevated pressure when combined with potassium. According to an unbiased structure searching method that combines first-principles calculations with particle swarm optimization algorithms, K3Ir in the Cu3Ti-type structure shows a favorable formation enthalpy (ΔH) compared to the elements and is dynamically stable above 10 GPa. This novel semiconductor (E g ≈ 1.6 eV) has sufficient orbital separation to allow complete charge transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Historically, it has had success in crystal structure predictions. 31,34,57,59,62,63 As mentioned above, DFT needs a starting structure to calculate energy. To generate this starting structure for DFT, there are multiple methods and algorithms available.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, it has had success in crystal structure predictions. 31,34,57,59,62,63 As mentioned above, DFT needs a starting structure to calculate energy. To generate this starting structure for DFT, there are multiple methods and algorithms available.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The most common software package used for DFT in crystal structure predictions is the Vienna Ab Initio Simulation Package, or VASP for short. Historically, it has had success in crystal structure predictions. ,,,,, As mentioned above, DFT needs a starting structure to calculate energy. To generate this starting structure for DFT, there are multiple methods and algorithms available.…”
Section: Introductionmentioning
confidence: 99%
“…Applying pressure minimizes interatomic distances, modifies the electronic structure and chemical bonding, and alters the fundamental rules of chemistry. Pressure also enables the formation of new phases that may be inaccessible under ambient conditions by shifting the thermodynamic potentials. As a result, high pressure has emerged as an essential approach for creating compounds with atypical stoichiometries and unusual physical properties. Yet, despite expanded access to high-pressure synthesis techniques, these experiments remain complex and uncommon. The many challenges associated with high-pressure synthesis and crystal structure analysis have led to the development of computational-based crystal structure prediction algorithms to understand the complex crystal chemistry of inorganic solids at nonambient pressure. …”
Section: Introductionmentioning
confidence: 99%
“…Computational studies have also suggested the formation of an iridide anion. The K–Ir binary system indicates a thermodynamically favorable K 3 Ir phase, albeit only at high pressure (10 GPa) . K 3 Ir is of great interest not only because it was the first predicted compound between an alkali metal and iridium but also because of iridium’s unusually large negative oxidation state (−1.64e – Ir).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that pressure is a fundamental thermodynamic variable that could be used as a powerful tool to investigate the physical and chemical properties of materials since it could significantly reduce interatomic distances and profoundly modifies electronic orbitals and chemical bonding, enabling the creation of exotic materials inaccessible under ambient conditions. For example, many novel lithium-rich compounds were found to become stable by exhibiting novel states at high pressure. Recent studies show that lithium atom doping could help chemically tune the valence states of some elements at high pressures, such as Li–Cs systems, , as well as design and discover the crystal structures of compounds inaccessible at ambient pressure.…”
mentioning
confidence: 99%